University Student’s Emotional States during Virtual Learning - Henritius, Eija; Hannula, Markku; Erästö, Panu; Salonen, Visajaani; Löfström, Erika (Frontline Learning Research, 2025)
This research examines students’ emotional states during a virtual course at a Finnish university. The mixed methods study drew on students’ self-reported commitment, self-efficacy, experienced emotions, and open-ended descriptions related to their emotions. The sample consisted of 85 students. Data were collected at nine measurement points during a half semester foundation course in statistics. Through latent profile analysis (LPA), we identified five distinct learner profiles described as the “Average”, “Struggling”, “Thriving”, “Victorious”, and “Determined”, and analyzed how they differ based on students’ gender, form of course implementation, previous attempts at the same course, and performance. Female students dominated in the “Average”, “Determined”, “Struggling”, and” Victorious” profiles. In all profiles, students mainly chose the blended learning implementation. In the “Struggling” profile, there were more students who had failed or had incomplete previous attempts at the course compared to other profiles. The students in the “Victorious” and “Thriving” profiles had the best exam results. The longitudinal design revealed distinct study experiences amongst the five profiles and pinpointed that most of the challenges took place in the middle of the course. The study contributes with understanding of the emotional challenges and challenges related to commitment- and self-efficacy in students’ learning process that could go unnoticed with fewer measurement points. The multi-measurement point approach along with the identification of emotion profiles makes a novel contribution to the field.